2018
DOI: 10.1111/desc.12656
|View full text |Cite
|
Sign up to set email alerts
|

Gesture for generalization: gesture facilitates flexible learning of words for actions on objects

Abstract: Verb learning is difficult for children (Gentner, ), partially because children have a bias to associate a novel verb not only with the action it represents, but also with the object on which it is learned (Kersten & Smith, ). Here we investigate how well 4- and 5-year-old children (N = 48) generalize novel verbs for actions on objects after doing or seeing the action (e.g., twisting a knob on an object) or after doing or seeing a gesture for the action (e.g., twisting in the air near an object). We find not o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
46
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(52 citation statements)
references
References 51 publications
6
46
0
Order By: Relevance
“…20 Future work is needed to explore whether children who learned through speech 1 gesture also show activation in regions associated with abstraction. If so, this would corroborate behavioral evidence 18,21 revealing that learning through gesture supports generalization better than learning through action on objects.…”
Section: Neurocognitive Underpinnings and Theorysupporting
confidence: 74%
See 1 more Smart Citation
“…20 Future work is needed to explore whether children who learned through speech 1 gesture also show activation in regions associated with abstraction. If so, this would corroborate behavioral evidence 18,21 revealing that learning through gesture supports generalization better than learning through action on objects.…”
Section: Neurocognitive Underpinnings and Theorysupporting
confidence: 74%
“…However, they were more likely to correctly identify "ratching" when it was performed on a new object if they had learned via gesture than via action. 18 In other words, seeing gesture (in this case, an iconic gesture that portrays an aspect of the word's meaning) increases the likelihood that a child will be able to generalize a newly learned word to a novel context.…”
Section: Theoretical Approaches For Intervention Learning From Othersmentioning
confidence: 99%
“…These iconic gestures can also play a role in word learning. One study taught toddlers novel words for novel actions (Wakefield, Hall, James, & Goldin-Meadow, 2018). The children were told either to produce a gesture for an action while learning a nonsense word for that action or to produce the action itself while learning the word.…”
Section: Learning Languagementioning
confidence: 99%
“…Seeing gesture as opposed to whole-body enactments boosted children's memory for how the actor moved. Further, Wakefield, Hall, James, and Goldin-Meadow (2018) found that seeing (or producing) gesture led children to more adeptly generalize the meaning of a novel verb than seeing (or producing) action. Thus, it appears that gesture may be uniquely situated to highlight information about manner of movement or particular movement patterns, whereas action emphasizes end state and goal-oriented parts of a movement event.…”
Section: Introductionmentioning
confidence: 97%